Alterations of Prefrontal-Posterior Information Processing Patterns in Autism Spectrum Disorders - Zhao, Hai-Chen; Lv, Rui; Zhang, Guang-Yu; He, Le-Min; Cai, Xiao-Tao; Sun, Qiang; Yan, Chun-Yan; Bao, Xiang-Yuan; Lv, Xin-Yue; Fu, Bin (Frontiers in Neuroscience, 2022)
Autism spectrum disorder (ASD) is a heterogeneous disorder characterized by different levels of repetitive and stereotypic behavior as well as deficits in social interaction and communication. In this current study, we explored the changes in cerebral neural activities in ASD. The purpose of this study is to investigate whether there exists a dysfunction of interactive information processing between the prefrontal cortex and posterior brain regions in ASD. We investigated the atypical connectivity and information flow between the prefrontal cortex and posterior brain regions in ASD utilizing the entropy connectivity (a kind of directional connectivity) method. Eighty-nine patients with ASD and 94 typical developing (TD) teenagers participated in this study. Two-sample t-tests revealed weakened interactive entropy connectivity between the prefrontal cortex and posterior brain regions. This result indicates that there exists interactive prefrontal-posterior underconnectivity in ASD, and this disorder might lead to less prior knowledge being used and updated. Our proposals highlighted that aforementioned atypical change might accelerate the deoptimization of brain networks in ASD.